The location of Tartessos: a fresh case for the reliability of Avienus’ Ora Maritima - Villarías-Robles, Juan J. R.; Rodríguez-Ramírez, Antonio; López-Sáez, José Antonio; Celestino-Pérez, Sebastián; León, Ángel (Frontiers in Marine Science, 2024)
Recent geomorphological, paleoenvironmental, and chronological evidence allows for a reconstruction of the coasts of southwest Iberia during the first millennium BCE that accords with descriptions of the region offered by authors of antiquity, most notably the description by the fourth-century CE Roman writer R. F. Avienus in his poem Ora Maritima. This poem contains information that appears to date from the sixth century BCE regarding, for instance, the pre-Roman polity of Tartessos. The reliability of this work as a historical source has been questioned for decades. Critics argue that the information is pertinent to our understanding of the literary, rather than historiographical, context of the Late Roman Empire. However, philological as well as historical analyses reveal no clear cause to doubt the documentary value of the Ora Maritima. Furthermore, geomorphological research makes it possible to identify most place-names in the poem; for example, the city embraced by the river Tartessos, apparently the political and trade center of the realm, may likely have stood on the present-day spit of La Algaida, which was an isle in the first millennium BCE. While this hypothesis has been advanced elsewhere, this article offers an entirely new set of evidences to support it.1